VIIaAT complexes, procoagulant phospholipids, and thrombin generation during postprandial lipemia. (22nd January 2018) - Silveira, A.; Carlo, A.; Adam, M.; McLeod, O.; Lundman, P.; Boquist, S.; Woodhams, B. J.; Hamsten, A.
Abstract: Introduction: Factor VII activation occurs postprandially. A proportion of activated factor VII (VIIa) circulates in complex with antithrombin (VIIaAT). Our primary objective was to assess the effects of postprandial lipemia on circulating VIIaAT, procoagulant phospholipid (PPL) activity, and thrombin generation. Methods: Plasma samples from postmyocardial infarction patients (n = 40) and controls (n = 39) were taken before and at 3 and 6 hours during a standardized oral fat tolerance test (OFTT). Fasting PPL activity measurements were also made in a second cohort of 108 postinfarction patients and 109 controls. VIIaAT was analyzed with the Asserachrom VIIaAT ELISA, PPL activity with the STA‐Procoag‐PPL kit, and thrombin generation with calibrated automated thrombogram with PRP‐Reagent as trigger (all Diagnostica Stago products). Results: Postprandially, VIIaAT increased in all samples without significant case‐control differences in the overall response during the OFTT. Thrombin generation measures peak height and velocity, and PPL activity, were marginally affected by the test meal in the controls. Levels of all patient baseline measures were significantly different from controls, indicating a more hypercoagulable state, and these differences were maintained throughout the OFTT. Fasting samples from cases showed higher PPL activity than control samples. Conclusion: Viewing VIIaAT quantitation as a surrogate for TF activity measurement, postprandial increase in VIIaAT may reflect a mechanism that adds to the cardiovascular risk associated with postprandial lipemia. On the other hand, the impact of postprandial lipemia on PPL activity and thrombin generation seems to be minor.